Leadership in Action : Issues and Observations - Staying Ahead of the Chaos Curve - Marshall, Edward M. (Center for Creative Leadership, 2010)
At work, individuals face enormous pressures. The chaos of the marketplace is often complemented by the chaos of the workplace. If only we could be grounded all the time, like an oak tree.